A Systematics Literature Review of SMEs Entrepreneurial Orientation - Pahlevi, Reza Widhar; Retnaningdiah, Dian; Kurnianingsih, Retno; Prasojo, Eko; Samsudin, Muhammad Agus (Universitas Negeri Semarang, 2022)
This study aims to analyze the systematic literature analysis of international scientific articles on the theme of SMEs entrepreneurial orientation research, data search from the perspective of keywords, research locations and subjects, as well as the research methods used. This study reviews 786 international articles and presents the main findings. First. The first theme in SMEs entrepreneurial orientation research is related to the concept of the right strategy that is very necessary for SMEs entrepreneurs, entrepreneurial orientation is one of the important factors that can drive the success of a business. Second, exploratory and case studies are the dominant data sets used. Third, research on entrepreneurial orientation in both developing and developed countries has almost the same number of studies. Fourth, based on bibliometric techniques using Vosviewer. Recommend further research agenda to exploring these four themes, it will further contribute to the development of SMEs entrepreneurial orientation in the future.